The coexistence of myosteatosis and the creatinine/cystatin C ratio are determinants of outcomes in cholangiocarcinoma patients undergoing curative surgery - Liu, Yan; Zhang, Jingli; Song, Guanghui; Ding, Xueli; Sun, Hui; Zhou, Jianrui; Jing, Xue (Frontiers in Oncology, 2024)
Background: Myosteatosis is a well-established predictor of poor prognosis in many types of cancer, and a decreased Creatinine/Cystatin C ratio (CCR) is a known indicator of unfavorable outcomes in patients with metabolic disorders and cancer. Despite this knowledge, the significance of concurrent CCR and myosteatosis in predicting the prognosis of patients with cholangiocarcinoma (CCA) who undergo radical surgery remains uncertain. Method: Data from 757 patients with cholangiocarcinoma who underwent the first radical resection in the Affiliated Hospital of Qingdao University from January 2017 to March 2022 were collected. According to the inclusion and exclusion criteria, 149 patients were finally included in the retrospective study cohort. Various clinicopathological, serological, and radiological data were collected at admission. Myosteatosis was evaluated using sliceOmatic software on computed tomography (CT) images. The study used receiver operating characteristic (ROC) curve analysis to determine the critical value of CCR, which predicts overall survival (OS) based on the Kaplan-Meier method. Univariate and multivariate Cox regression analyses were employed to identify the risk factors associated with OS and RFS confidently. Results: The group identified as the myosteatosis cohort consisted of 79 patients with an average age of 64.3 ± 7.8 years. The ROC curve analysis revealed an optimal critical CCR value of 10.834. A low CCR ≤ 10.834 and myosteatosis were found to be associated with poor OS and RFS outcomes (P = 0.022; P = 0.017; P = 0.038; P = 0.030 respectively). Moreover, patients with myosteatosis and a CCR ≤ 10.834 had the worst OS and RFS outcomes (P = 0.035; P = 0.027). Conclusion: After radical excision in CCA patients, the presence of myosteatosis and CCR had a negative correlation with prognosis. A more accurate prediction of OS and RFS was possible by combining CCR and myosteatosis, compared to CCR alone.